2004
DOI: 10.1016/s1078-5884(03)00561-6
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal Hypertension and its Relationship to Sac Thrombus: A Semi-qualitative Analysis by Experimental Fluid Mechanics

Abstract: Objectives. To ascertain the effect of aneurysm thrombus and luminal diameter on arterial blood pressure within the abdominal aortic aneurysm lumen and at the sac wall. Methods. A lifelike abdominal aortic aneurysm was incorporated in a pulsatile flow unit, using systemic blood pressure settings of 140/100 mmHg and 130/90 mmHg (denoted the high and low settings, respectively). Aneurysm sac pressure was measured in the absence of thrombus within the sac. This was repeated after a thrombus analogue (gelatine) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
(15 reference statements)
1
5
0
Order By: Relevance
“…We also considered the ILT as a single layer due to these constraints. This approach is consistent with previously published experimental modelling of AAA [11,12,19,20]. From the uniaxial tensile testing we determined that our ILT analogues had Young’s modulus of 0.24Mpa (ILT1) and 0.33MPa (ILT2) which is similar to values for the medial layer found by Wang et al [38].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We also considered the ILT as a single layer due to these constraints. This approach is consistent with previously published experimental modelling of AAA [11,12,19,20]. From the uniaxial tensile testing we determined that our ILT analogues had Young’s modulus of 0.24Mpa (ILT1) and 0.33MPa (ILT2) which is similar to values for the medial layer found by Wang et al [38].…”
Section: Discussionsupporting
confidence: 91%
“…The primary limitation of this study is the idealisation of considering the ILT and the artery wall as single layers. While this is a gross assumption, it is less significant than using ILT analogues without investigating their mechanical properties, as previously reported [11,12,41]. We believe that our simplified one layer ILT analogue is more representative than materials such as dough or gelatin.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…On the other hand, there is still some concern regarding the protective role of ILT, since many authors who evaluated in vivo the influence of ILT on intraluminal pressure transmission reported that the presence of ILT fails to reduce the transmission of intraluminal pressure on the AAA wall, consequently leaving the risk of AAA rupture unaffected. 18,19 The above has been reported to hold true even in thrombosed aneurysms. 2026…”
Section: Role Of Intraluminal Thrombusmentioning
confidence: 81%